Can We Identify Patients with High Risk of Osteoarthritis Progression Who Will Respond to Treatment? A Focus on Biomarkers and Frailty - Arden, Nigel (2015)
Funding: This meeting was founded by the European Society for Clinical and Economics Aspect of Osteoporosis and Osteoarthritis, a not for profit organization from Belgium.